A low power CMOS transmitter with Class-E power amplifiers for positioning application in multi-band - Hsieh, Chia-Yu; Röber, Jürgen; Bänisch, Andreas; Hagelauer, Amelie Marietta; Ußmüller, Thomas; Weigel, Robert (GeMiC 2016, German Microwave Conference 2016, 2016)
In this paper, a transmitter for outdoor positioning application such as animal tracking is introduced. Class-E power amplifiers are exploited in the transmitter system in order to increase the energy efficiency for the demand of long operation duration of the system. Along with the need of power saving, a circuit topology is proposed to realize the modulation based on Binary Offset Carrier (BOC) technique at two different bands to achieve higher positioning accuracy and better utilization of the spectrum by transmitting data simultaneously. The operating frequencies of the system are 868 MHz and 2.4 GHz, and the circuit is designed in 150nm CMOS technology. The power efficiency of the class-E power amplifier is greater than 50 % over 2.4-2.8 GHz while the measured output power is greater than 10 dBm from 1.3 to 2.8 GHz.
elib2cris::1512001600,hsieh2016
Keywords: positioning; class-E

Measurement of Backscatter RFID-Transponders - Ußmüller, Thomas; Brenk, Daniel; Essel, Jochen; Hsieh, Chia-Yu; Fischer, Georg; Weigel, Robert (14th IEEE International Workshop on Signal Processing Advances in Wireless Communications, 2013)
elib2cris::1512001600,ussmueller2013a

Miniaturized sensor nodes with mutual detection and localization capability - Hierold, Martin; Hsieh, Chia-Yu; Weigel, Robert; Kölpin, Alexander (German Microwave Conference (GeMic), 2015)
Severe restrictions in size and weight of mobile nodes intended for the observation of bats result in strict limitations of their power supply. A sensor node and system design for proximity detection in bats observation considering these constraints with first field test results is presented in this talk. For further miniaturization and specific adjustment to the target application a custom system on chip solution is proposed. Its hardware design is outlined addressing energy efficiency, localization and reconfiguration capability.
elib2cris::1512001600,hierold2015b
Keywords: wireless sensor network; low power

Protocol Design for Ultra-Low Power Wake-Up Systems for Tracking Bats in the Wild - Dressler, Falko; Blössl, Bastian; Hierold, Martin; Hsieh, Chia-Yu; Nowak, Thorsten; Weigel, Robert; Kölpin, Alexander (EEE International Conference on Communications (ICC 2015), 2015)